Influence of mixture compositions on ion energy distributions in Ar/N2 electron cyclotron resonance plasma. (September 2015) - Zhang, Y.C.; Xie, X.H.; Li, H.; Yang, K.; Tang, Z.L.; Zhu, X.D.
Abstract: In this report, the mass and energy spectra of ions in Ar/N2 electron cyclotron resonance (ECR) plasma at the microwave power of 100 W and the gas pressure of 1 Pa are investigated by a Hiden EQP analyzer, and also the plasma optical emission spectra are recorded by optical emission spectroscopy (OES). Singly charged Ar + and N2 + as the dominant ions are detected. The ion energy distribution functions (IEDFs) of Ar + and N2 + exhibit complicated evolutions of peak structures with varying the N2 fractions. The IEDF of Ar + is bimodal at the low N2 fractions, and changes to trimodal structure as the N2 fractions are near 40%. However, it turns to be unimodal at the N2 fractions above 80%. The IEDFs of N2 + present unimodal structures in the case of both high and low N2 fractions, and the bimodal profiles appear as the N2 fractions are around 50%. It is suggested that the distributed ionization and the charge–exchange reactions between ions and neutrals are responsible for the evolutions of peak structures for IEDFs. Highlights: The mass and energy spectra of ions in ECR Ar/N2 plasma are investigated. Mixture compositions will induce changes in the shape of ion energy distributions. The distributed ionization and charge–exchange reactions are main mechanisms.